2005
DOI: 10.1021/ed082p1174
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Demonstrations as the Laboratory Component in Nonscience Majors Courses. An Outreach-Targeted Approach

Abstract: In place of traditional cookbook laboratory exercises, a nonmajors' chemistry course uses a demonstration-focused laboratory to understand basic chemical theories. Each student spends the lab session preparing, practicing, and learning the chemistry of two unique demonstrations. By selecting demonstrations of different concepts, the students cover the same breadth and type of themes as a traditional laboratory in a new and exciting format. Twice during the semester, students from the course prepare and present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Of course, questions of how these techniques were used and with what populations often moderated the results. In some studies, demonstrations have been shown to help with attention (e.g., ref ), and understanding (e.g., ref ). Demonstrations were of interest in this study.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Of course, questions of how these techniques were used and with what populations often moderated the results. In some studies, demonstrations have been shown to help with attention (e.g., ref ), and understanding (e.g., ref ). Demonstrations were of interest in this study.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Chemistry courses for nonmajors are important curricular contributions as they play a key role in improving scientific literacy of undergraduates . Nonmajors chemistry courses give instructors opportunities to explore creative use of themes, and published examples include use of art, food chemistry, medicinal chemistry, , and popular culture. Additional reports detail successful pedagogical approaches used in nonmajors courses, such as community outreach, , innovative projects, learning communities, and travel components. ,,, While most published work focuses on face-to-face courses, teaching nonmajors in a fully online course can allow for greater flexibility for both students and instructors, especially when taught asynchronously. Laboratory projects can be completed at home through such approaches as preassembled kits, household chemicals, and simulations. Additional creative approaches no doubt were developed in early 2020 when instructors had to quickly pivot from face-to-face classrooms and laboratories to remote delivery, and readers are encouraged to consult the Journal for additional suggestions.…”
Section: Institution and Course Backgroundmentioning
confidence: 99%
“…In certain cases, devising new chemistry activities has led to publication. , College students also earn service hours at the outreach events by presenting lessons to the elementary students, helping to set up and tear down experiments or just being present to help supervise young students. Service learning of this type seems to be quite a successful approach to scientific community outreach, and had been employed at a number of institutions. At SAU, many students work hours beyond the required 5 h, and education majors particularly appreciate the chance to teach science concepts to elementary and middle school students.…”
Section: Description Of Science Outreach In the Communitymentioning
confidence: 99%
“…Unfortunately, chemists at many academic institutions are reluctant to participate in outreach endeavors . We therefore applaud the efforts of chemical educators and chemistry students who are involved in presenting science to the public, providing interesting, hands-on chemistry experiments for young people to explore (see, for example, refs ). We are similarly motivated by a desire to interest elementary and middle school students to excel in mathematics and science.…”
mentioning
confidence: 99%